Donör Bölgeye Trombositten Zengin Plazma İnfiltrasyonunun Toplanan Yağ Greftleri Üzerindeki Etkileri - Ergün S.; Durgun U.; Yıldız K.; Güler E. M. (My University, 2022)
Fat grafting is a frequently performed procedure in plastic surgery. There are numerous studies conducted with the goal of increasing the survival rate of an existing fat graft at the recipient area. In our research, we have discovered that stimulating the fat tissue at the donor area with biological auxiliary factors and putting it through the priming process prior to harvesting for the purpose of boosting the survival rate of the graft weren’t in the literature. In our study, the purpose was to reveal the changes caused by the infiltration of platelet-rich plasma (PRP) to the donor area as well as its effect on the survival rate of fat grafts in rats, using various parameters.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)